2012
DOI: 10.5194/hess-16-741-2012
|View full text |Cite
|
Sign up to set email alerts
|

A combined field and modeling study of groundwater flow in a tidal marsh

Abstract: Abstract. Bald mud beaches were found among the mangrove marshes in Dongzhaigang National Nature Reserve, Hainan, China. To investigate the possible reasons for this phenomenon, the intertidal zones of a mangrove transect and a bald beach transect with similar topography and tidal actions were selected for comparison study. Along both transects, observed water table variations were significant in the high and low intertidal zones and negligible in the middle intertidal zones. Despite the same tidal actions and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 67 publications
2
25
0
Order By: Relevance
“…The tidal contribution to SGD was estimated to be ∼20 m 3 d −1 m −1 . Xia and Li (2012) quantified the tide-induced SGD in a tidal marsh using the numerical code MARUN, which was ∼6.0 m 3 d −1 m −1 with no inland freshwater recharge. The seepage face development was also ignored.…”
Section: Introductionmentioning
confidence: 99%
“…The tidal contribution to SGD was estimated to be ∼20 m 3 d −1 m −1 . Xia and Li (2012) quantified the tide-induced SGD in a tidal marsh using the numerical code MARUN, which was ∼6.0 m 3 d −1 m −1 with no inland freshwater recharge. The seepage face development was also ignored.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 6(a) and (c)) the tidal contribution to SGD can be estimated to be ~20 m 2 /d. In 2012, Xia and Li [42] used the numerical model MARUN reproduced the field observed watertable in two transects (one is mangrove transect and the other is tidal flat) in mangrove marshes in Dongzhaigang National Nature Reserve, Hainan, China. They identified that both transects have a mud-sand two-layered structure: a surface zone of low-permeability mud and an underlying high permeability zone that outcrops at the high and low tide lines.…”
Section: Tide-induced Sgd From Beach Aquifersmentioning
confidence: 99%
“…During the circulation of seawater, seawater mixes with the terrestrially-derived groundwater and chemicals, leading to various biogeochemical interactions in the pore water in rocks and soils. Therefore, SGD is an important source of nutrients, contaminants, chemicals and trace elements to the coastal waters [1,24,[38][39][40] and has considerable impact on the quality and the ecosystem of the receiving seawater [41][42][43][44].…”
mentioning
confidence: 99%
“…A series of experiments conducted in gravel beaches of Prince William Sound, Alaska, indicated that the twolayered structure of a high-permeability surface layer underlain by a low-permeability layer had significant impacts on the persistence of spilled oil ( Guo et al, 2010;Li and Boufadel, 2010; . Xia and Li ( 2012 ) made a comparative study between a bald beach and a mangrove beach with similar topography and tidal actions in the intertidal zones of Dongzhaigang in Haikou City of Hainan Province, indicating that the inland freshwater recharge and the mud-sand two-layered structure played key roles in the development of mangrove and their spatial distribution. Ma et al ( 2015 ) developed a simple method ( " single-well method" ) for estimating seawater-groundwater exchange rate in a silty beach, taking into account the effects of seepage face and density and based on field measurements of groundwater hydraulic head, temperature and salinity.…”
Section: Introductionmentioning
confidence: 99%
“…Seepage meters were also used to estimated SGD at local area, such as manual seepage instrument developed by Cable et al ( 1997 ) , heat pulse seepage meter developed by Taniguchi and Fukuo (1993) and ultrasonic flow meter developed by Paulsen et al (2001) . Numerical simulations usually focused on limited coastal transect, such as Guo et al (2010) , , Xia and Li (2012) , Xia et al (2010) .…”
Section: Introductionmentioning
confidence: 99%